Post-operative management of lateral knee snapping syndrome: A case study: Lateral knee snapping syndrome - Chinnavan, Elanchezhian; Kolangarakath, Rineesh; Shashidharan, Srisha; S. Aldablan, Abdullah; S. Natarajan, Vijay (Manual Therapy, Posturology & Rehabilitation Journal, 2025)
Background: Snaps are caused by the rapid displacement of an anatomic or pathologic structure when an adjacent joint moves. Lateral knee snapping or snapping of the biceps femoris tendon is uncommon. The tendon snaps over the fibular head when it is being flexed or extended. Objec-tive: This study was undertaken because there is limited evidence in the literature regarding the benefits of physical therapy after biceps femoris surgery for treatment of lateral knee syndrome. Methodology: A 27-year-old man had been having clicking sounds in his left leg for 3 years. The condition had been diagnosed medically and physically as snapping of the biceps femoris ten-don, and biceps reinsertion surgery had been performed. This study was carried for 8 months. The agility T-test and the International Knee Documentation Committee (IKDC) score were used to evaluate the outcome of a rehabilitation regimen. The rehabilitation was administered three times a week for 16 weeks and once a month for another 16 weeks, and the condition of the pa-tient was monitored. Results: The IKDC score was 18.3% and the agility T-test score 13.50 sec-onds at the initial evaluation after the biceps femoris reinsertion. After 16 weeks of physical therapy, the patient’s IKDC score was 83.9% and the agility t test score was 9.50 seconds. After 32 weeks the IKDC score was 91.9% and the T-test score was 7.90 seconds. Conclusion: A rehabilita-tion strategy is beneficial after biceps femoris tendon surgery. It reduces pain and stiffness and improves the range of motion, functional ability, and sports performance.